ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN BADAN PELAYANAN PERIJINAN TERPADU (BPPT) KABUPATEN BADUNG - Wira Sutha, I G. A. Ketut; Thanaya, I N. Arya; Yansen, I W. (JURNAL SPEKTRAN; Vol. 2, No.2, Juli 2014, 2014)
In order to give a more efficient and effective public service, the Badung government formed a Board for Integrated Permit Services (BPPT) as stipulated by the Local Government Regulation Number 4 / 2013 on 21 March 2013 which started its service on 1 May 2013. They used community’s satisfaction as a measure in order to give a good quality of services which is evaluated periodically. This study purposeful to know the community’s satisfaction level of BPPT services in order to know the effect of the five quality dimension of services which are tangibility, reliability, responsiveness, assurance and empathy. Quisioner method were use to collect data, which are contain 25 questions descriptivetly about the fact and realization of BPPT services regarding to the ninety six customers. And inferential analysis method were use to get conclusion about population based on behavior. The conclusion of descriptive analysis mention that the satisfaction level of community regarding to the overall of BPPT services is 66.98% value with category of “sufficiently satisfactory” where the most influential dimension of the community’s satisfaction was Empathy with the coefficient of 0.787 as shown in the regression equation Y = 15.133 + 0.630X 1 + 0.463X 2 + 0.659X 3 + 0.602X 4 + 0.787X 5. The inferential analysis method mention that five dimension influence simultaneously dan partially to the community’s satisfaction. The suggestions that can be given from this study is to opptimalyzed the supporting facilities with providing a centre of communication which is usually called “call centre”, so easly for the community to get information and to propose critic and suggest regarding to the services.
Keywords: BPPT of Badung Regency, community’s satisfaction, simultaneously, partially, call centre.